Robotic hysterectomy using the Vessel Sealer for myomatous uteri: technique and clinical outcome. (November 2015) - Hoste, Griet; Van Trappen, Philippe
Abstract: Objective: Robotic procedures using the Vessel Sealer are not well reported in the literature, especially given the advantages of sealing devices already studied in standard laparoscopic procedures. This study reports our experience with the EndoWrist ® One™ Vessel Sealer in robotic hysterectomy for myomatous uteri. Study design: In this retrospective cohort study of the first 50 consecutive patients with myomatous uteri undergoing a robotic hysterectomy, we report our experience with the EndoWrist ® One™ Vessel Sealer (Intuitive Surgical Inc., Sunnyvale, CA) during this procedure. The learning curve was evaluated, and the operative times as well as the complications were recorded. Results: After the first 10 cases, the median console and total (skin-to-skin) operative time dropped significantly from 110 to 60 min and from 158 to 105 min, respectively ( p  = 0.018 and p  = 0.008 respectively). The body mass index (≤ or >30 kg/m 2 ), uterine weight (≤ or >250 g), and uterine size had no statistical significant effect on the total operative time. Median blood loss during surgery was 63 mL in all cases (range: 0–400 mL). The morbidity was low, and approximately 50% of cases could be discharged from the hospital after one to two days. Conclusion: Robotic hysterectomy using the Vessel Sealer has, after a short learning curve of 10 cases, similar operative times than other published reports on robotic hysterectomy or laparoscopic hysterectomy using a sealing device for myomatous or large uteri.